Numerical Simulation Study on Aeroacoustic Characteristics within Deformable Cavities. (7th March 2019) - Fangli, Ning; Shunshan, Ning; Changtong, Zhang; Zhe, Liu
Abstract : Cavity flow phenomena are encountered in many kinds of aviation vehicles. The flow-induced noise can easily cause structure resonance and fatigue damages. Therefore, the study on the mechanism and effective control methods of cavity noise are very important to engineering applications. A new active control method was proposed based on the deformable cavity in order to mitigate the cavity noise. Large eddy simulation (LES) and computational aeroacoustics (CAA) are combined to simulate a typical open cavity noise. The results show the first mode sound-pressure level (SPL) of tonal noise decreases gradually while the first mode frequency sharply jumps within a small range of the slant angle of the trailing and bottom wall. In addition, with the increase in the slant angle, the decrease of the first mode SPL of tonal noise at Mach 0.6 is more significant than that at Mach 0.85, but the increase of the first mode frequency at Mach 0.85 is more dramatical than that at Mach 0.6. The proposed method can not only reduce the first mode SPL obviously but also increase the first mode frequency dramatically, which makes it different from the natural frequency of the cavity structure and sequentially helps the cavity avoid fatigue damages from resonance.